1987
DOI: 10.3109/01050398709074941
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Monaural, Binaural and No Amplification in Subjects with Bilateral Hearing Loss

Abstract: This study expands upon our earlier work by comparing initial PB scores and audiometric thresholds with results obtained 4-17 years later for subjects with bilateral sensorineural hearing losses who were monaurally aided (n = 48), binaurally aided (n = 19), or unaided (n = 19). Thresholds decreased slightly for all groups, but aided and unaided ears did not differ significantly in this respect, revealing no acoustic trauma effect due to hearing aid use. PB scores decreased significantly only for the unaided ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
1
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 18 publications
6
25
1
5
Order By: Relevance
“…Word-recognition-in-noise scores at presentation levels between 65 and 90 dB sound pressure level (SPL) were compared in 24 monaurally aided subjects. Results at the highest intensity levels replicated those of Silman et al [43] and Gelfand et al [44], such that the aided ear performed better than the unaided ear. In contrast, at lower levels the finding was the opposite.…”
Section: Asymmetrical Hearing Created By Monaural Amplificationsupporting
confidence: 79%
See 1 more Smart Citation
“…Word-recognition-in-noise scores at presentation levels between 65 and 90 dB sound pressure level (SPL) were compared in 24 monaurally aided subjects. Results at the highest intensity levels replicated those of Silman et al [43] and Gelfand et al [44], such that the aided ear performed better than the unaided ear. In contrast, at lower levels the finding was the opposite.…”
Section: Asymmetrical Hearing Created By Monaural Amplificationsupporting
confidence: 79%
“…Individuals using binaural amplification or no amplification did not show an interaural difference. This finding was referred to as "lateonset auditory deprivation" and was further substantiated by other studies [44][45][46], as well as by studies in children [47][48]. Evidence that effects of auditory deprivation are associated with amplification fit to only one ear were supported by the 1995 Eriksholm Workshop on Auditory Deprivation and Acclimatization [49].…”
Section: Asymmetrical Hearing Created By Monaural Amplificationsupporting
confidence: 57%
“…Different aspects of the bene t of bilateral HA use have been reported: better subjective rating of sound quality with two HAs (McKenzie & Rice, 1990; Balfour & Hawkins, 1992), better word recognition scores for bilateral HA users (McKenzie & Rice, 1990;Feuerstein, 1992) and reduction of problems associated with tinnitus (Brooks & Bulmer, 1981). Besides these described advantages of bilateral ampli cation, there are reports about negative long-term effects of unilateral ampli cation (Gelfand et al, 1987;Burkey & Arkis, 1993;Gelfand, 1995;Hurley, 1999). In these studies an auditory deprivation effect for the unaided ear has been reported.…”
Section: Introductionmentioning
confidence: 93%
“…Some previous reports (Silman et al, 1984(Silman et al, , 1992Gelfand et al, 1987;Dieroff et al, 1989;Gatehouse, 1989;Silverman et al, 1990) claim that deterioration of speech discrimination is more rapid in the unaided ears, when monaural tting is being used. According to Silman et al (1992) this occurs in 40% of the unaided ears.…”
Section: Introductionmentioning
confidence: 94%